Young People versus Competition in the Contemporary World - Jarosław Antoni Bąbka (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction   The author defines here the concept of competition and presents the mechanism of how competition permeates through schools which act as a habitat for the functioning of young people. Reference is made to the ecological concept of human development by Urie Bronfenbrenner, assumptions of neoliberalism, as well as to over modernity as a stage in development of a society. The author analysed the differences between women and men in terms of evolution and social and cultural attitudes.  Purpose of research The purpose of the present paper is to present opinions of young people, the representatives of the Z generation, on competition in the modern world as well as to state whether there are differences between attitudes shown by women and men. Research method The author obtained the research results by means of a diagnostic survey carried out among young people attending a secondary technical school in a medium sized town. In order to calculate the relation between the variables  the  χ2 test was used and the statistical programme SPSS - PS Imago version 5.0 was applied.   Results The research shows that young people experience competition and its negative effects. Competition among those surveyed plays mainly a role of a tool for influencing the group.  Young people accept competition which acts as a source of satisfaction and motivation for action, yet they do not exclude the need for cooperation. The differences between the opinions shared by men and women on competition were found to be statistically significant. Men were more competition oriented than women. Men, in a situation of defeat, more often declared the feeling of anger and humiliation, whereas women felt rather underestimated.  Women more often than men, focused on such effects that competition had on psychosocial functioning such as panic, stress, disturbances of thinking and the perception of one's own situation. Conlusions When stepping towards young people experience competition, function by following the rules of competition and accept it, though they do not skip cooperation. Young people experience negative effects that  rivalry has on their mental and physical condition. The survey shows that women were worse in finding themselves in situations involving competition. This means that it is necessary to suplement prevention progrmmes with issues related to competition, the ambivalence of masculinity and feminity patterns and to improve students' emotional resistance.